Pengaruh Penggunaan Tiktok Terhadap Ketergantungan Mahasiswa Dalam Mengakses Informasi Berita Politik - Muhammad Azka Huwaidi; Vera Nur Azizah; Yuni Afita Sari (Cakra Communico: Journal of Communication Science, 2024)
TikTok is an online social media platform based on music videos, offering unique and attractive special effects. It has now become one of the most popular social media platforms across all age groups. It can be said that the current generation is dependent on this app, using TikTok as a medium or source of information, where the first source of information is often obtained through this platform. The diversity of information affects the accuracy and trustworthiness of the information circulating on this platform for the current generation. The purpose of this study is to determine whether TikTok influences the dependence of students in Malang on accessing political news information. This quantitative research uses a survey method, with data collected through questionnaires from a total of 117 student respondents in Malang. The results show an influence between variable (X) and variable (Y), explaining that TikTok as an information medium impacts students' level of dependence by 69.5%. It can be concluded that TikTok can help individuals meet their information needs, and the more one uses this social media, the higher their level of dependence becomes.